Penerapan Metode Composite Performance Index (CPI) Dalam Proses Penentuan Penerima Bantuan Program Bedah Rumah Bagi Keluarga Miskin Dikota Lubuklinggau - Budi Santoso Budi Santoso; Armanto (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Lubuklinggau City is one of the major cities located in South Sumatra Province. As one of the big cities, Lubuklinggau City also has a classic problem that is shared by other big cities in general. The problem is poverty. One of the efforts made by the Lubuklinggau City Government in collaboration with the central government in poverty alleviation efforts is to conduct a house renovation program for poor households in the city of Lubuklinggau. In implementing the determination of the recipient of the house renovation program, what often happens is that the agency appointed to determine the recipient of the house reconstruction program assistance has difficulty in determining who has the right to receive and who does not. The implementation of Decision Support System (SPK) using the Composite Performance Index (CPI) method is one of the solutions to overcome existing problems. The Composite Performance Index (CPI) method uses a method of solving problems with the Multiple Criteria Decision Making (MCDM) system which determines the order or priority in multicriteria analysis. The final result of this system is to display ranking data of people who are entitled to receive assistance from the government house renovation program.